Experimental investigation of methane storage on MIL-101 - Tan, Joseph Jin Wee (2017)
In the recent years, the level of carbon dioxide and methane levels in the atmosphere has been on the rise and this has caused global warming to be a concern in the future. The increase in demand for fossil fuels has caused many to use other alternatives of energy sources such as natural gases (NG). These global issues have led to researchers to start discovering different methods to adsorb methane and carbon dioxide. One of the methods is to use metal organic frameworks (MOF). Storing of Liquefied Natural Gases (LNG) and Compressed Natural Gases (CNG) have their individual limitations and dangerous hazards, hence making Adsorbed Natural Gases (ANG) the ideal for methane storage.